2016
DOI: 10.1111/febs.13644
|View full text |Cite
|
Sign up to set email alerts
|

Formation and removal of poly‐ubiquitin chains in the regulation of tumor necrosis factor‐induced gene activation and cell death

Abstract: Tumor necrosis factor (TNF) is a potent cytokine known for its involvement in inflammation, repression of tumorigenesis and activation of immune cells. Consequently, accurate regulation of the TNF signaling pathway is crucial to prevent potent noxious effects of TNF. These pathological conditions include chronic inflammation, septic shock, cachexia and cancer. The TNF signaling cascade utilizes a complex network of post-translational modifications to control the cellular response following its activation. Next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 130 publications
(226 reference statements)
0
38
0
Order By: Relevance
“…Because SPATA2 also requires HOIP for its recruitment to the NOD2-SC, we deem it likely that the complex consisting of LUBAC, SPATA2, and CYLD is the default complex recruited also to other receptor-associated complexes known to involve CYLD and/or LUBAC (Douanne et al., 2016, Tauriello et al., 2010). Given the growing relevance of the equilibrium between ubiquitination and deubiquitination in the regulation of signaling complexes (Harhaj and Dixit, 2012, Kupka et al., 2016, Yau and Rape, 2016) and the involvement of CYLD in a wide number of signaling platforms (Draber et al., 2015, Mathis et al., 2015, Reiley et al., 2006, Tauriello et al., 2010, Zhang et al., 2011), the discovery of SPATA2 as a previously unrecognized adaptor between CYLD and HOIP by us and others (Wagner et al., 2016) provides additional insight on the mechanisms by which this DUB controls the outcome of these diverse signaling processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because SPATA2 also requires HOIP for its recruitment to the NOD2-SC, we deem it likely that the complex consisting of LUBAC, SPATA2, and CYLD is the default complex recruited also to other receptor-associated complexes known to involve CYLD and/or LUBAC (Douanne et al., 2016, Tauriello et al., 2010). Given the growing relevance of the equilibrium between ubiquitination and deubiquitination in the regulation of signaling complexes (Harhaj and Dixit, 2012, Kupka et al., 2016, Yau and Rape, 2016) and the involvement of CYLD in a wide number of signaling platforms (Draber et al., 2015, Mathis et al., 2015, Reiley et al., 2006, Tauriello et al., 2010, Zhang et al., 2011), the discovery of SPATA2 as a previously unrecognized adaptor between CYLD and HOIP by us and others (Wagner et al., 2016) provides additional insight on the mechanisms by which this DUB controls the outcome of these diverse signaling processes.…”
Section: Discussionmentioning
confidence: 99%
“…The differently linked types of ubiquitin chains are generated by specific E3s and are degraded by specialized DUBs. Hence, precise timing of the respective activities of these enzymes is paramount for fine regulation of the signaling output generated by ubiquitin-involving signaling complexes (SCs) (Chen and Sun, 2009, Kupka et al., 2016, Zinngrebe et al., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…A20 is a bi-functional enzyme that acts on RIP1 both as an ubiquitin protease for K63-linked ubiquitin chains and as an ubiquitin ligase that attaches K48 ubiquitinlinked chains, which promotes the degradation of RIP1 [35, 36]. CYLD was identified as a de-ubiquitinating protease that targets RIP1 and releases its K63-linked ubiquitin chains, thereby decreases the stability of NF-κB pathway as well as enhances cell death by promoting the formation of caspase 8 [37]. In our study, although I3C did not change the expression of A20, it stimulated the protein expression of CYLD in a dose-dependent manner, which suggested that the induction of CYLD contributes to the inhibition to RIP1 K63 ubiquitination by I3C.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, formation of RSCs and activation of the Ub-and kinase-dependent signalling cascades leads to activation of NF-jB transcription factors and pro-inflammatory transcriptional programmes (Jiang & Chen, 2012). However, for TNF-R1, it can also lead to cell death via formation of a TRADD-, FADD-, RIPK1/3-and caspase-8-containing death-inducing complex, complex-II (Fuchs & Steller, 2015;Kupka et al, 2016b). Recent research has shown that M1-linked Ub chains are key in determining the fate of a cell upon TNF stimulation.…”
Section: Introductionmentioning
confidence: 99%